The association between the romantic relationships of parents and offspring depressive symptoms: Mediating effects of offspring communication patterns and romantic relationships - Li, Na; Zhang, Yi-Meng; Xiong, Na-Na; Sun, Qi-Qing; Qian, Ying; Sun, Hong-Qiang (Frontiers in Psychology, 2022)
This study investigated a conceptual model by testing how parental romantic relationships influenced the depressive symptoms of grown-up children and whether the constructive communication patterns of grown-up children and romantic relationships played mediation effects within it. A total of 421 Chinese participants were enrolled in the study. The level of depressive symptoms, romantic relationship satisfaction and closeness, couple communication patterns, and parental romantic relationships were measured via self-report questionnaires. According to the results, the structural equation modeling analysis verified that the severity of participants’ depressive symptoms was negatively associated with the parental romantic relationship and that the association was mediated by participants’ constructive communication patterns and their own romantic relationships. Furthermore, compared with nondepressed participants, depressed participants were less satisfied with their parental romantic relationships, exhibited fewer constructive communication patterns and were more distant and unsatisfied with current romantic relationships.